2012
DOI: 10.1186/1471-2490-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of MMP-9 and IL-8 are correlated with poor prognosis of Bladder Cancer

Abstract: BackgroundExtracellular matrix homeostasis is strictly maintained by a coordinated balance between the expression of metalloproteinases (MMPs) and their inhibitors. The purpose of this study was to investigate whether the expression of MMP-9, MMP-2 and its specific inhibitors, are expressed in a reproducible, specific pattern and if the profiles are related to prognosis in Bladder Cancer (BC).MethodsMMP-9, MMP-2 and its specific inhibitors expression levels were analyzed by quantitative real-time polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 19 publications
3
57
0
9
Order By: Relevance
“…The present findings are consistent with previous studies, which suggested that MMP-9 plays a role in bladder cancer (56,57). The present study identified that the expression rates of MMP-9 in bladder cancer patients was significantly increased compared with healthy control individuals (6,9).…”
Section: A B Csupporting
confidence: 83%
“…The present findings are consistent with previous studies, which suggested that MMP-9 plays a role in bladder cancer (56,57). The present study identified that the expression rates of MMP-9 in bladder cancer patients was significantly increased compared with healthy control individuals (6,9).…”
Section: A B Csupporting
confidence: 83%
“…Furthermore, the differentially expressed genes in CAFs following treatment with chemotherapy may be important in modulating the function of tumor cells, and subsequently participate in chemoresistance correspondingly. Based the present study, IL8, a multifunctional chemokine secreted by multiple cell types (including monocytes, endothelial cells, fibroblasts and tumor cells), has been frequently reported to be closely associated with cancer development and poor prognosis (7,8,18). The exact role of IL8 in regulating tumor cell behavior remains unclear.…”
Section: Discussionmentioning
confidence: 80%
“…The expression of MMP-9 and MMP-2 has been implicated in the development and progression of many neoplasms, such as prostate, colorectal, and lung cancer (REIS et al, 2012). Mantena et al (2005) showed that green tea polyphenols are promising as anticarcinogenic agents because these compounds prevent the development of solar UV radiationinduced skin cancer and reduce the expression of MMP-9 and MMP-2.…”
Section: Resultsmentioning
confidence: 99%
“…Within the family of human MMPs, the matrix metalloproteinase 2 (MMP-2) (gelatinase A, 72 kDa) and matrix metalloproteinase 9 (MMP-9) (gelatinase B, 92 kDa) cleave, among other components, type IV collagen and gelatin, which are the main structural components of the basal membrane (REIS et al, 2012). With the exception of membrane-type MMPs, these enzymes are secreted as latent pro-enzymes and are usually regulated by endogenous tissue inhibitors of the matrix metalloproteinase (TIMPs) (WALTER et al, 2005).…”
Section: Introductionmentioning
confidence: 99%